Intraoperative techniques in realtime ureteric navigation. A brief narrative review and a video vignette - Jayasinghe, Jayan Dewantha; Butnari, Valentin; Hu, Kylin Weiguang; Thaha, Mohamed Adhnan (Frontiers in Surgery, 2025)
BackgroundIntraoperative ureteric injury, a well-documented but avoidable adverse event in pelvic surgery, is sometimes associated with low surgical volume and inexperience of the surgeon. The current literature describes several techniques that can help surgeons identify and protect the ureter during pelvic dissection, especially during complex procedures or repeat surgeries. This narrative review aims to highlight and present the currently available techniques for intraoperative ureteric identification in colorectal surgery and showcase the use of Indocyanine Green (ICG) in real-time ureter identification using a video vignette.MethodsA literature search of the PubMed database was performed from inception until May 14, 2025, to identify relevant articles reporting on intraoperative ureteric navigation techniques in colorectal surgery. Articles were analysed if they described the application of a technique in colorectal surgical procedures to identify the ureter intraoperatively. Given the narrative nature of this review, a qualitative synthesis was conducted by identifying the key themes described. In a video, we demonstrate a case of laparoscopic Hartmann's reversal of how ICG can facilitate surgical steps and the outcomes of a challenging procedure.ResultsTechniques to identify the ureter intraoperatively during colorectal surgery were identified and discussed: (1) Image-Guided Techniques comprising Fluorescence Imaging and Use of Intraoperative Ultrasound; (2) Computer-Assisted and Augmented Reality Navigation consisting of 3D Model-Based Navigation, Augmented Reality, and Artificial Intelligence; and (3) Mechanical or Physical Identification Aid. These techniques highlight the improved outcomes in complex colorectal surgeries by preventing ureteric injury while enhancing the training process, even in complex, redo surgeries.ConclusionOur narrative review highlights that image-guided surgery and augmented reality techniques are rapidly evolving in colorectal surgery. Our video vignette shows that intraoperative ureteric navigation makes challenging adhesiolysis easier and safer, which subsequently facilitates the training process in benign complex or re-do minimally invasive pelvic surgery.